2017
DOI: 10.1177/1938965517704532
|View full text |Cite
|
Sign up to set email alerts
|

How Do Investments in Human Resource Management Practices Affect Firm-Specific Risk in the Restaurant Industry?

Abstract: Despite the importance of achieving a competitive advantage in human resources in the restaurant industry, restaurant firms often hesitate to make significant investments in human resource management (HRM) practices because of outcome uncertainty, operational issues, and limited financial resources, among other issues. Building upon the strategic human resource management (SHRM) literature, the current study attempts to better understand the HRM issues in the restaurant industry and investigate the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 77 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…In response to a large body of theoretical and philosophical statements on CSR, many hospitality researchers have empirically tested the effect of hospitality firms' CSR initiatives on various factors such as customer satisfaction, financial performance and risk (Kang et al, 2010;Kim and Kim, 2014;Park et al, 2017aPark et al, , 2017b. However, those studies have remained too intricate to draw a definitive conclusion.…”
Section: Literature Review Definition and Theories Behind Csrmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to a large body of theoretical and philosophical statements on CSR, many hospitality researchers have empirically tested the effect of hospitality firms' CSR initiatives on various factors such as customer satisfaction, financial performance and risk (Kang et al, 2010;Kim and Kim, 2014;Park et al, 2017aPark et al, , 2017b. However, those studies have remained too intricate to draw a definitive conclusion.…”
Section: Literature Review Definition and Theories Behind Csrmentioning
confidence: 99%
“…A recent study reported that Fortune Global 500 companies spend approximately $15bn annually on CSR initiatives (Davidson et al, 2016). Although the restaurant industry is facing many challenges, such as high operating costs, high sensitivity to economic conditions, low profit margins, and relatively high risk (Jogaratnam, 2017;Ottenbacher and Harrington, 2009), CSR investment is considered an imperative because it has significant impacts on both internal and external stakeholders in various ways (Kang et al, 2016;Park et al, 2017aPark et al, , 2017b. For instance, CSR initiatives can be used as an instrument for businesses to differentiate themselves from their competitors, especially in the restaurant industry, where inter-firm rivalries are intense (McWilliams et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It also spans from discussing opportunities and barriers to attracting new hotel workers in the context of CSR (McGinley et al , 2017), to the positive financial impact of hospitality businesses' investment on diversity in recruitment and selection (Singal, 2014). Finally, yet importantly, there are studies (Park et al , 2017) that look at how socially responsible human resource management (HRM) practices influence unsystematic risk in hospitality businesses. As much as employees have been central to non-shareholding stakeholders' studies on CSR in hospitality, they have been framed as policy addressees or policy implementers.…”
Section: Introductionmentioning
confidence: 99%